2018
DOI: 10.3390/biomedicines6040101
|View full text |Cite
|
Sign up to set email alerts
|

Notch and Wnt Dysregulation and Its Relevance for Breast Cancer and Tumor Initiation

Abstract: Breast cancer is the second leading cause of cancer deaths among women in the world. Treatment has been improved and, in combination with early detection, this has resulted in reduced mortality rates. Further improvement in therapy development is however warranted. This will be particularly important for certain sub-classes of breast cancer, such as triple-negative breast cancer, where currently no specific therapies are available. An important therapy development focus emerges from the notion that dysregulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 142 publications
(166 reference statements)
0
20
0
Order By: Relevance
“…Specifically, Notch signaling pathway is involved in mammary development and homeostasis as well as in the promotion of breast cancer when dysregulated [34]. Indeed, accumulating evidence sustains the importance of Notch pathway in mammary stem cells (MaSCs) generation and maintenance during mammary gland development [35].…”
Section: Notch Signaling Overview In Tnbcmentioning
confidence: 99%
“…Specifically, Notch signaling pathway is involved in mammary development and homeostasis as well as in the promotion of breast cancer when dysregulated [34]. Indeed, accumulating evidence sustains the importance of Notch pathway in mammary stem cells (MaSCs) generation and maintenance during mammary gland development [35].…”
Section: Notch Signaling Overview In Tnbcmentioning
confidence: 99%
“…Physiological regulators such as Notch receptors and ligands, along with Wnt ligands, can induce EMT in mammary epithelial cells. Notch and Wnt factors are also important for different steps of breast cancer initiation and progression [29,30,31,32,33]. In addition, EMT in normal mammary epithelial cells can be induced by overexpression of the apoptosis regulator B-cell lymphoma/leukemia gene 2 (BCL2), highlighting a novel role of BCL2 in EMT [34].…”
Section: Breast Cancer Subtypes and Their Association With Emtmentioning
confidence: 99%
“…Prior study also reported that dysregulation and decrease in NOTCH signaling pathway are associated with endometriosis (Su et al, 2015; González-Foruria et al, 2017). NOTCH3 has also been reported as a major driver for breast cancer development (Braune et al, 2018). It plays an important role in maintaining the tumor phenotype in pancreatic ductal adenocarcinoma (PDAC) (Song et al, 2018), lung carcinogenesis (Su et al, 2018), and endometrial carcinoma (Mitsuhashi et al, 2012).…”
Section: Discussionmentioning
confidence: 99%